Features of the Mechanism of Development and Course of Pneumonia Under Exposure to the Organism of Pesticides - Kurambaev Yakhshimurat Bekzhanovich,; Karimova Zevara Khadzhibaevna (Zien Journals, 2022)
The aim of presented work is to study the features of mecha- nism of the development and course of experimental pneumonia against a back- ground of body intoxication by pesticide of OPC - antio group.
Keywords: pesticide; pneumonia; organophosphorous compound; antio